KOMUNIKASI KELUARGA ETNIS BETAWI DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK DI WILAYAH JAKARTA, BOGOR, DEPOK DAN TANGERANG - Maulina Larasati Putri; Ayu Priana (Metakom, 2020)
The family is the first party that plays the most role in the formation of various aspects of a child's life, one of which is learning motivation. The purpose of this research is to find out how Betawi ethnic family communication can improve children's learning motivation. This research uses descriptive research method with a qualitative approach. The primary data collection method is done by interview, while secondary data is obtained from various sources of journal articles, books, theses, and other research documents similar to this research. The results of this study found that, Betawi ethnic families with consensual and pluralistic family types tended to be able to increase children's learning motivation. Whereas families with protective types tend not to increase children's learning motivation, and there are no informants with laissez-faire family types. The contribution of this study is the result of research that can be applied by Betawi ethnic and other ethnic families to be able to know and apply suitable family types to increase children's learning motivation